Corpus Callosotomy for Intractable Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The results of corpus callosotomy in 18 patients 16 years old and younger are reported from the Sections of Neurology and Neurosurgery, Dartmouth-Hitchcock Medical Center, Hanover, NH.